Equality and Choice: Sex Equality Perspectives on Reproduction Rights in the Work of Ruth Bader Ginsburg - Siegel, Reva B. (Columbia Journal of Gender and Law, 2013)
This brief essay explores the sex-equality perspective on reproductive rights that Ruth Bader Ginsburg has articulated over four decades as lawyer, law professor, judge, and Justice. Throughout her career, Ginsburg has viewed laws that deprive women of control over whether and when they bear children as raising questions of equality, as well as liberty and privacy. Ginsburg and other feminists of the 1970s argued that, given the social organization of caregiving work, the state may not deprive women of control over the decision to become mothers without depriving them of equal citizenship.